Possible association between SP-C mutations and lung cancer: Two case reports and review of literature. (2021) - Darawshy, Fares; Rmeileh, Ayman Abu; Kuint, Rottem; Berkman, Neville
Highlights: Mutations in the SP-C gene are rare. Mutations in the SP-C gene are associated with interstitial lung disease. Patients with SP-C mutations should be considered at increased risk for the development of lung cancer. Abstract: Surfactant protein C (SP-C) is one of four surfactant proteins produced by type II pneumocytes. Mutations in surfactant protein A are strongly associated with development of lung cancer. Mutations in the SP-C gene are rare and are associated with interstitial lung disease in the pediatric age group. We describe two patients with SP-C mutations who developed lung cancer. Both patients had concurrent interstitial lung disease, although the clinical phenotype was variable. In both cases, mutations were in translated region of the SP-C gene; one in the BRICHOS domain and the other in the transmembrane domain. Our paper suggests that patients with SP-C mutations can be at increased risk for the development of lung cancer, and it's reasonable to follow them routinely.